Serotonin 2C Receptor as a Superhero: Diversities and Talents in the RNA Universe for Editing, Variant, Small RNA and Other Expected Functional RNAs - Michihisa Tohda (Elsevier, 2014)
Abstract.: The serotonin 2C receptor subtype (5-HT2C) has a unique profession and continues to provide exciting and critical new information. The 5-HT2C is modulated at the RNA level by several mechanisms, including editing, short variant generation, and small RNAs. Recently, these phenomena, which had been demonstrated individually, were shown to be associated with each other. At present, many reports provide information about the influence of RNA regulation on receptor protein activities and expression, which was thought to be the final functional product. However, complicated behavior at the RNA stage allows us to imagine that the RNA itself has functional roles in the RNA universe. The 5-HT2C RNA may play several roles. This review will outline previous 5-HT2C studies and prospects for future studies. Keywords:: serotonin 2C receptor subtype (5-HT2C), RNA universe, RNA editing, small RNA, functional mental disease (FMD)